Focusing on lower extremity DVT. Issue 4 (April 2016) - D'Alesandro, MaryAnn
Abstract : Protect hospitalized patients from the highly preventable and sometimes deadly complications of deep vein thrombosis, including pulmonary embolism. Make sure you're current on evidence-based practices presented here to prevent death and disability.